Pengembangan Produk Susu yang Mengandung Kalsium, Inulin, dan Teripang sebagai Susu Kaya Prebiotik dan Kolagen - Almira Nadia; Mirza Hapsari Sakti Titis Penggalih; Emy Huriyati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
One of the health problems that happens in elderly is osteoporosis. Its prevalence in Indonesia reached 19.7%. Nutrition is one of the important parts of osteoporosis treatment. Sufficient calcium intake impacts on high bone density. Many factors affect calcium absorption. Inulin is a prebiotic that helps increase calcium absorption. Bone composition is one of the important factors. Collagen is a bone component besides calcium and phosphate, which improves fracture resistance. The research aims to determine the organoleptic and physicochemical properties of a dairy product named